The NagY regulator: A member of the BglG/SacY antiterminator family conserved in Enterococcus faecalis and involved in virulence - Soussan, Diane; Salze, Marine; Ledormand, Pierre; Sauvageot, Nicolas; Boukerb, Amine; Lesouhaitier, Olivier; Fichant, Gwennaele; Rincé, Alain; Quentin, Yves; Muller, Cécile (Frontiers in Microbiology, 2023)
Enterococcus faecalis is a commensal bacterium of the gastrointestinal tract but also a major nosocomial pathogen. This bacterium uses regulators like BglG/SacY family of transcriptional antiterminators to adapt its metabolism during host colonization. In this report, we investigated the role of the BglG/SacY family antiterminator NagY in the regulation of the nagY-nagE operon in presence of N-acetylglucosamine, with nagE encoding a transporter of this carbohydrate, as well as the expression of the virulence factor HylA. We showed that this last protein is involved in biofilm formation and glycosaminoglycans degradation, that are important features in bacterial infection, confirmed in the Galleria mellonella model. In order to elucidate the evolution of these actors, we performed phylogenomic analyses on E. faecalis and Enterococcaceae genomes, identified orthologous sequences of NagY, NagE and HylA, and we report their taxonomic distribution. The study of the conservation of the upstream region of nagY and hylA genes showed that the molecular mechanism of NagY regulation involves ribonucleic antiterminator sequence overlapping a rho-independent terminator, suggesting a regulation conforming to the canonical model of BglG/SacY family antiterminators. In the perspective of opportunism understanding, we offer new insights into the mechanism of host sensing thanks to the NagY antiterminator and its targets expression.